379 Do Depressive Symptoms Mediate the Association Between Insomnia and Physical Activity?. (3rd May 2021) - Walker, Jamie; Campbell, Rebecca; Vargas, Ivan
Abstract: Introduction: Insomnia and depression are highly comorbid and have been shown to be independently associated with lower levels of physical activity. It is not clear, however, if being less physically active is a risk factor for or consequence of depression and insomnia. The factors that explain the associations between insomnia, depression, and physical activity are likely complex and overlapping. For example, insomnia may predict inactivity by impacting one's energy levels, leaving them too tired to exercise. Insomnia may also interfere with one's motivation to exercise due to low mood, as insomnia is associated with the development of depressive symptoms. The purpose of the present study was to explore whether depression mediated the link between insomnia and low levels of physical activity. Methods: A national online survey was conducted from April-June 2020. Participants completed surveys to assess demographics, mood, sleep, and physical activity. Depressive symptoms were estimated with the Center for Epidemiologic Studies Depression Scale (CES-D). Insomnia symptoms were estimated with the Insomnia Severity Index (ISI). Physical activity levels were estimated with the International Physical Activity Questionnaire (IPAQ). Analyses were conducted using multiple linear regression, with separate models for depression, insomnia, and the combination of the two, on levels of physical activity. Results: 3, 952 adults (Mage = 46.9 years) completed the survey. According to the unadjusted models, greater insomnia symptoms were associated with greater depressive symptoms (b = 0.4523, SE = 0.019593, p < .001), and lower levels of physical activity (b = -38.741, SE = 18.236, p = 0.0337). The relationship between insomnia and physical activity was no longer significant, however, when controlling for depression (b = -6.140, SE = 19.274, p = 0.75). According to the mediation analyses, there was an indirect effect of insomnia on physical activity that was explained by differences in depressive symptoms (Sobel Test = -4.895, SE = 6.518, p < .001). Conclusion: Our findings support previous research indicating associations between symptoms of insomnia and depression and physical activity. Future research should examine if these same results hold using a longitudinal design. Support (if any): Vargas: K23HL141581